Answer:
The answer is circle; (x')² + (y')² - 4 = 0
Explanation:
* At first lets talk about the general form of the conic equation
- Ax² + Bxy + Cy² + Dx + Ey + F = 0
∵ B² - 4AC < 0 , if a conic exists, it will be either a circle or an ellipse.
∵ B² - 4AC = 0 , if a conic exists, it will be a parabola.
∵ B² - 4AC > 0 , if a conic exists, it will be a hyperbola.
* Now we will study our equation:
* 2x² + 2y² = 8
∵ A = 2 , B = 0 , C = 2
∴ B² - 4AC = (0) - 4(2)(2) = -16 < 0
∵ B² - 4AC < 0
∴ it will be either a circle or an ellipse
* Lets use this note to chose the correct figure
- If A and C are equal and nonzero and have the same sign,
then the graph is a circle.
- If A and C are nonzero, have the same sign, and are not equal
to each other, then the graph is an ellipse.
∵ A = 2 and C = 2
∴ The graph is a circle.
∵ D and E = 0
∴ The center of the circle is the origin (0 , 0)
∵ Ф = 30°
∴ The point (x , y) will be (x' , y')
- Where x = x'cosФ - y' sinФ and y = x'sinФ + y'cosФ
∴ x = x'cos(30°) - y'sin(30°)
∴ y = x'sin(30°) + y'cos(30°)
∴ x = (√3/2)x' - (1/2)y' and y = (1/2)x' + (√3/2)y'
∴
![x=(√(3)x'-y')/(2)](https://img.qammunity.org/2020/formulas/mathematics/high-school/wcpnv4cjr1m11txp03uontmk3qkjb8hu5m.png)
∴
![y=(x'+√(3)y')/(2)](https://img.qammunity.org/2020/formulas/mathematics/high-school/n64tcv9113q9ak1tuo6fbffm56ic11593q.png)
* Lets substitute x and y in the first equation
∴
![2((√(3)x'-y')/(2))^(2)+2((x'+√(3)y')/(2))^(2)=8](https://img.qammunity.org/2020/formulas/mathematics/high-school/y8bnu0mjvqdiyfzbh40z2ohvgo4cj61lnp.png)
* Use the foil method
∴
![2((3x'^(2)-2√(3)x'y'+y'^(2))/(4))+2((x'^(2)+2√(3)x'y'+3y'^(2))/(4))=8](https://img.qammunity.org/2020/formulas/mathematics/high-school/wpgv3dplse2fer1azisazid9zv4y2g48ya.png)
* Open the brackets
∴
![(3x'^(2)-2√(3)x'y'+y'^(2)+x'^(2)+2√(3)x'y'+3y'^(2))/(2)=8](https://img.qammunity.org/2020/formulas/mathematics/high-school/h21nvzxzc3lrwu7o822vuwokq19m92mx59.png)
* Collect the like terms
∴
![(4x'^(2)+4y'^(2))/(2)=8](https://img.qammunity.org/2020/formulas/mathematics/high-school/2ig2xu39po05xfhr3xwky5ge8yt3ai25x6.png)
* Simplify the fraction
∴ 2(x')² + 2(y')²= 8
* Divide each side by 2
∴ (x')² + (y')² = 4
∴ The equation of the circle is (x')² + (y')² = 4
* The general equation of the circle is (x')² + (y')² - 4 = 0
after rotation 30° about the origin
* Look to the graph
- The blue circle for the equation 2x² + 2y² = 8
- The blue circle for equation (x')² + (y')² - 4 = 0
* That is because the two circles have same centers and radii
- The green line is x' and the purple line is y'